World Bank Group Support to Public-Private Partnerships : Lessons from Experience in Client Countries, FY02-12 - Independent Evaluation Group (World Bank Group, Washington, DC, 2015)
The World Bank Group (WBG) commends the independent evaluation group's (IEG) evaluation of the Group's support to public-private partnerships (PPP). Under its new strategy, the WBG intends to work with the public and private sectors to end extreme poverty and promote shared prosperity and seeks to increase synergies across the Bank Group. Client countries are increasingly interested in PPP arrangements to provide badly needed public services, and PPPs are, by their nature, a prime area for close WBG collaboration. Management believes that IEG has presented a balanced account of WBG support to its client countries during the period of FY2002-12. Management is in general agreement with the report's recommendations. The management action record presents management s response to individual recommendations.